Modifiable Risk Factors for Alzheimer’s Disease - Edwards III, George A.; Gamez, Nazaret; Escobedo Jr., Gabriel; Calderon, Olivia; Moreno-Gonzalez, Ines (Frontiers in Aging Neuroscience, 2019)
Since first described in the early 1900s, Alzheimer’s disease (AD) has risen exponentially in prevalence and concern. Research still drives to understand the etiology and pathogenesis of this disease and what risk factors can attribute to AD. With a majority of AD cases being of sporadic origin, the increasing exponential growth of an aged population and a lack of treatment, it is imperative to discover an easy accessible preventative method for AD. Some risk factors can increase the propensity of AD such as aging, sex, and genetics. Moreover, there are also modifiable risk factors - in terms of treatable medical conditions and lifestyle choices - that play a role in developing AD. These risk factors have their own biological mechanisms that may contribute to AD etiology and pathological consequences. In this review, we will discuss modifiable risk factors and discuss the current literature of how each of these factors interplay into AD development and progression and if strategically analyzed and treated, could aid in protection against this neurodegenerative disease.